Is body dissatisfaction related to an attentional bias towards low weight bodies in non-clinical samples of women? A systematic review and meta-analysis. (March 2023) - House, T.; Graham, K.; Ellis, B.; Bould, H.; Attwood, A.S.; Stephen, I.D.; Brooks, K.R.; Penton-Voak, I.S.
Abstract: Body dissatisfaction is defined as the negative subjective evaluation of one's body and is considered a risk factor for, and symptom of, eating disorders. Some studies show women with high body dissatisfaction display an attentional bias towards low weight bodies; however, this finding is not consistent, and results are yet to be systematically synthesised. We conducted a qualitative and quantitative synthesis of cross-sectional studies investigating the relationship between body dissatisfaction and attentional bias to low weight bodies in non-clinical samples of women. We searched PubMed, Scopus, Web of Science, PsycINFO, ProQuest, and OpenGrey for studies up until September 2022. We identified 34 eligible studies involving a total of 2857 women. A meta-analysis of 26 studies (75 effects) found some evidence from gaze tracking studies for a positive association between body dissatisfaction and attentional bias to low weight bodies. We found no evidence for an association from studies measuring attention using the dot probe task, electroencephalogram (EEG) recording, or the modified spatial cueing task. The results together provide partial support for the positive association between body dissatisfaction and attentional bias to low weight bodies in women. These findings can be used to inform future attentional bias research. Highlights: We systematically reviewed and meta-analysed studies measuring attentional bias. Body dissatisfaction was positively associated with attention to low weight bodies. However, only gaze tracking studies found compelling evidence for the association. The results may be limited by publication bias. The results can inform future attentional bias research.